(Genetic Studies for Leptin in Hypertensive Patients in Thi-Qar Governorate/ Iraq) - Assala Salam Jebur; Mohammed A. Auda; Dhyaa Khalaf (University of Thi-Qar Journal of Science, 2021)
The current study showed a high frequency of AA genotype compared to the AC and CC genotypes in patients and control group. In the control group, 71.11% had AA genotype, 22.22% were heterozygote and had AC genotype and 6.67% had CC genotype. However, 53.33% of patients had AA genotype, 40.00% had AC genotype and 6.67% had CC genotype. Odd ratio increased by 2.40 times in AC compared to AA genotype (wild type) as a reference with a significant difference between patients and control group (OR 2.40, 95% CI 0.66 – 4.51). While, there was no significant differences between CC genotype and AA genotype in patients and control group (OR 1.33, 95% CI 0.24 – 7.19).